Social media use and negative body image perception in Saudi Arabian women - Maha AlQahtani; Maha AlQahtani; Narmeen Shaikh; Khabir Ahmad; Noara Alhusseini (Frontiers in Public Health)
BackgroundSocial media has become deeply embedded in daily life, particularly among females who spend significant time on visual-based platforms such as Snapchat, and Instagram. Exposure to unrealistic beauty standards on these platforms has been linked to negative body image, a growing global public health concern with well-documented psychological and behavioral consequences. While this relationship has been widely studied globally, research within Saudi Arabia, especially among adult women beyond early adulthood, remains limited.ObjectiveThis study aimed to examine the association between social media use and body image perception among adult females in Saudi Arabia, while accounting for relevant factors such as sociodemographic characteristics, BMI, and beauty filter use.MethodsAn online cross-sectional survey was conducted among adult females (aged ≥ 18) in Saudi Arabia. Validated instruments—the Social Media Addiction Scale-14 and the Body Image Questionnaire—were used to assess social media addiction and negative body image, respectively. Associations were examined using Poisson regression with robust variance.ResultsOf the 1,136 participants, 71.2% were classified as having a negative body image. Participants with social media addiction severity and BMI outside the normal range (underweight, overweight, or obese) had significantly higher rates of negative body image (p < 0.001). In contrast, using beauty filters showed no significant association with negative body image.ConclusionNegative body image is highly prevalent among adult females in Saudi Arabia and is significantly associated with both social media and higher body mass index. These findings highlight the need for culturally appropriate interventions to improve body acceptance.